Children and television - Gunter, Barrie; McAleer, Jill. (London ; New York : Routledge, 1997)
What is the nature of children's viewing? Why do children watch TV? How do children watch TV? How well do children follow and understand TV? Does TV improve children's knowledge?...
Keywords: Children; Television; Television and children -- Great Britain